Efforts To Improve Alpinia Galanga Production Capability In The Prosperous Plantation Group In Red Mata Village, Banyuasin I Sub-District, Banyuasin District - Nainggolan, Immer Togarma; Fatoni, Herawan; Mutaqin, Azhadi; Hadjri, Muhammad Ichsan (International Journal of Scientific Research and Management (IJSRM), 2024)
This study aims to determine and analyze the improvement of  alpinia galanga production capabilities in the Makmur Sejahtera Plantation Group, Merah Mata Village, Banyuasin I District, Banyuasin Regency. This program is a flagship Corporate Social Responsibility (CSR) program of PT PLN Indonesia Power Merah Mata Generating Unit called Kampung Alpinia galanga, which raises the issue of community empowerment. This program aims to develop management activities, production, and distribution of Alpinia galanga agricultural products and support government programs regarding food security in the communities around PLTG Borang. The method used in this research is a qualitative approach with a descriptive method. The Alpinia galanga Village program has been running since 2021 by PT PLN Indonesia Power UP Merah Mata PLTG Borang. Initial planning was carried out to determine the program's roadmap to be implemented through collaboration between PLTG Borang and the  alpinia galanga Village Group. The program scheme that is run together is a long-term empowerment program. After the development of  alpinia galanga agricultural commodities and the manufacture of  alpinia galanga derivative products, farmers are trained to market Alpinia galanga derivatives/product branding, one of the innovations of Alpinia galanga village. PT PLN Indonesia Power UP Merah Mata PLTG Borang runs the Kampung Alpinia galanga mentoring program for residents on an ongoing basis to encourage the economy of residents, as evidenced by the increase in average income from IDR 600,000 to IDR 3,438,679, which reduces poverty by 3.33% in Merah Mata Village in 2023.